(untitled) (Cardiovascular Journal, 2011)
A 19-year-old primigravida was diagnosed to have complete heart block (CHB) during her antenatal checkup at 36 weeks. The patient had history of syncope a few years back. She was referred to the National Institute of Cardiovascular Diseases (NICVD). A temporary pacemaker was implanted at NICVD. She was then referred to Dhaka Medical College Hospital (DMCH), where a baby girl was delivered by cesarean section. A permanent pacemaker was implanted later at NICVD. To our knowledge this is the first case report of pace maker implantation in a pregnant woman from Bangladesh. Key Words: Congenital complete heart block; Pregnancy; Pacemaker. DOI: http://dx.doi.org/10.3329/cardio.v1i2.8179 Cardiovasc. j. 2009; 1(2) : 237-239